Extracellular matrix molecules play diverse roles in the growth and guidance of central nervous system axons - M.A. Pires-Neto; S. Braga-de-Souza; R. Lent (Brazilian Journal of Medical and Biological Research, 1999)
Axon growth and guidance represent complex biological processes in which probably intervene diverse sets of molecular cues that allow for the appropriate wiring of the central nervous system (CNS). The extracellular matrix (ECM) represents a major contributor of molecular signals either diffusible or membrane-bound that may regulate different stages of neural development. Some of the brain ECM molecules form tridimensional structures (tunnels and boundaries) that appear during time- and space-regulated events, possibly playing relevant roles in the control of axon elongation and pathfinding. This short review focuses mainly on the recognized roles played by proteoglycans, laminin, fibronectin and tenascin in axonal development during ontogenesis.